Prevalence of chronic venous insufficiency and deep vein thrombosis in cirrhotic patients - da Cruz Renó, Leonardo; Tustumi, Francisco; Waisberg, Daniel Reis; Santos, Vinicious Rocha; Pinheiro, Rafael Soares; Macedo, Rubens Arantes; Nacif, Lucas Souto; Ducatti, Liliana; De Martino, Rodrigo Bronze; Trevisan, Alexandre Maximiniano; D’Albuquerque, Luiz Carneiro; Andraus, Wellington (Frontiers in Medicine, 2023)
Summary People with cirrhosis of the liver are at risk for complications that can worsen their quality of life and increase morbidity and mortality. Contrary to previous beliefs, cirrhosis does not protect against the development of thromboembolic events, and cirrhotic patients may have higher rates of deep vein thrombosis (DVT). Background and aims The study of chronic venous disease and its impact on patients with cirrhosis is unknown in the literature and may be an important fact since this condition also had impact on quality of life and morbidity. The aim of this study is to evaluate the prevalence of DVT (Deep Venous thrombosis) in outpatients with cirrhosis and the degree of chronic venous insufficiency, evaluating possible correlations between clinical and laboratory aspects of cirrhotic patients with these pathologies. Methods Patients with cirrhosis were evaluated in the outpatient clinic of the Liver Transplantation and Hepatology Service of HC-FMUSP from November 2018 to November 2022, with clinical evaluation, venous disease questionnaires, data collection of imaging and laboratory tests, and venous color Doppler ultrasound. The information was analyzed by the University of São Paulo (USP) Statistics Department. Results There was a prevalence of 7.6% of DVT in studied patients, VCSS score 6.73 and severe CEAP classification (C4-6) 32.1%. There was no association of DVT with qualitative variables by the Fisher test such as Child Turcotte Pugh Scale (CTP) (p = 0.890), dichotomized INR values (p = 0.804), etiology of cirrhosis (p = 0.650) and chronic kidney disease (p > 0.999), nor with quantitative variables by t-student’s such as age (p = 0.974), Body Mass Index (BMI) (p = 0.997), MELD score (p = 0.555), Albumin (p = 0.150) and Platelets (p = 0.403). We found that as the severity of ascites increases, there is an increase in the proportion of patients classified in the category indicating more severe clinical manifestations of chronic venous disease (C4 to C6). The mean age (54 years) was higher in patients with DVT than in those without. The mean BMI of patients without DVT (25.7 kg/m2) is lower than that of patients with DVT (27.0 kg/m2). The prevalence of DVT is higher in patients with thrombophilia (20.0%) than in those without (7.0%). This suggests an association between the two variables. The descriptive measures of the MELD score, the cirrhosis scale used for liver transplant waiting lists, did not indicate an association of this scale with the occurrence of DVT. Conclusion The incidence of VTE (Venous Thromboembolic Events) and CVD (Chronic Venous Disease) within the sample surpassed that of the general population; nevertheless, more studies are required to validate these results. Concerning venous thromboembolism, no correlation was observed between the variables within the sample and the augmented risk of VTE. Regarding chronic venous disease, studies have shown that edema and orthostatism are correlated with increased severity of CVD on the VCSS scales. Statistical dispersion methods suggest that patients with higher BMI and more severe liver disease (according to the Child-Pugh score) are more likely to experience worsening of CVD. About chronic venous disease, studies have shown that edema and orthostatism are correlated with increased severity of CVD on the VCSS scales.